Pengaruh Kepemimpinan serta Kompensasi terhadap Motivasi Atlet Esports Pelatda Provinsi Sumatera Utara - Sagala, Tamado Simon (Majalah Ilmiah METHODA, 2024)
Esports is an official sports branch in Indonesia, as stated in the results of the KONI National Working Meeting (RAKERNA) in 2020, which declared esports to be part of the prestigious sports branch. This is also in line with the establishment of the Indonesian Esports Association (PBESI) as the governing body of electronic sports under the National Sports Committee of Indonesia (KONI). Research results show that the t-value of both variables is below 0.005, and F calculated is greater than F table (570.063 > 2.91). It can be explained that leadership has a significant positive influence on the achievement motivation of esports athletes in the provincial training center (Pelatda) of North Sumatra. Compensation also has a significant positive influence on the achievement motivation of esports athletes in the provincial training center (Pelatda) of North Sumatra partially. Furthermore, it is found that both leadership and compensation have a significant positive influence on the achievement motivation of esports athletes in the provincial training center (Pelatda) of North Sumatra simultaneously.